172k views
0 votes
Let
m=x^(2)+3

Which equation is equivalent to
(x^(2)+3)^(2) +7x^(2) +21=-10

A.)
m^(2)-7m+10=0
B.)
m^(2)-7m+31=0
C.)
m^(2)+7m+10=0
D.)
m^(2)+7m+31=0

1 Answer

7 votes

Answer:


{m}^(2) +7m + 28 = 0

Explanation:

Given that,


m = {x}^(2) + 3

We know that,


{x}^(2) = m- 3

Now look at the sum


( {x}^(2) + 3) ^(2) + 7 {x}^(2) + 21 = - 10 \\


( {x}^(2) + 3) ^(2) + 7 {x}^(2) + 21 = - 10 \\ {m}^(2) + 7 * m- 3 + 21 = - 10 \\ {m}^(2) +7m + 18= - 10 \\ {m}^(2) + 7m + 18+ 10 = 0 \\ {m}^(2) + 7m + 28 = 0

User Mattpx
by
7.4k points